2018
DOI: 10.3389/fpls.2018.01313
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Candidate Genes for Enhancing Grain Zn Concentration in Wheat

Abstract: Wheat (Triticum aestivum L.) is one of the major staple food crops worldwide. Despite efforts in improving wheat quality, micronutrient levels are still below the optimal range for human nutrition. In particular, zinc (Zn) deficiency is a widespread problem in human nutrition in countries relying mainly on a cereal diet; hence improving Zn accumulation in grains is an imperative need. This study was designed to understand the genetic architecture of Zn grain concentrations in wheat grains. We performed a genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
46
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 54 publications
11
46
0
Order By: Relevance
“…In the present study, after comparing both the GLM, MLM, and FarmCPU models, MLM appeared to be the best choice to perform a GWAS analysis on Zn grain accumulation. These results were in accordance with previous GWAS studies for Zn grain accumulation in wheat [29,30], where the association analysis was performed using the mixed linear model. Slight differences were observed among the Zn concentrations in the grains of the association population planted in different locations, which may be attributed to varying environmental conditions of different locations ( Figure 1A).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In the present study, after comparing both the GLM, MLM, and FarmCPU models, MLM appeared to be the best choice to perform a GWAS analysis on Zn grain accumulation. These results were in accordance with previous GWAS studies for Zn grain accumulation in wheat [29,30], where the association analysis was performed using the mixed linear model. Slight differences were observed among the Zn concentrations in the grains of the association population planted in different locations, which may be attributed to varying environmental conditions of different locations ( Figure 1A).…”
Section: Discussionsupporting
confidence: 91%
“…Specifically, in the study conducted by Velu et al [29] were identified major effect QTL on the 2 and 7 group chromosomes using a population of 330 spring common wheat varieties. In the study conducted by Alomari et al [30], markers associated with greater Zn accumulation were identified across the majority of the chromosomes but were concentrated on chromosomes 3B and 5A.…”
Section: Introductionmentioning
confidence: 93%
“…The QQ plots for SNP results revealed that the distribution of observed association p -values were close to the distribution of expected associations (Figure 4B and Figure 5B); that means the model which we implemented for GWAS was sufficiently stringent to control for false positive associations. In a previous study a total of 8 markers in the whole panel and 31 markers in the subpanel (Tables S3 and S4) had been found significant for grain Zn concentration in the same germplasm [9]. Based on BLUEs, significant markers from the whole and subpanel were selected for a query against IWGSC RefSeq annotation v1.0 to get their annotations.…”
Section: Resultsmentioning
confidence: 99%
“…A population comprised of 369 elite European wheat varieties including 355 genotypes of winter wheat and 14 genotypes of spring wheat, mainly from Germany and France was used in this study. Field experiments were carried out at IPK, Gatersleben, Germany over three consecutive years (2014/2015, 2015/2016 and 2016/2017) using plot with a size of 2 × 2 m for each genotype with six rows spaced 0.20 m apart and more details were described in a previous study by Alomari et al [9]. The grains were collected randomly from more than 250 plants of each plot to be used in the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation